To Evaluate the Relationship Between Antenatal Bladder wall Thickness and the Subsequent Development of Post-Ablation Detrusor Underactivity in Children with Posterior Urethral Valves - Mohsin Zaman, Zulfiqar Saeed, Hinna Qayum, Muhammad Kamran Khan, Muzzamil Sohail, Shehzad Faiz (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the relationship between antenatal bladder wall thickness and the subsequent development of post-ablation detrusor underactivity in children with posterior urethral valves. Methods: This prospective observational study was conducted at the Paediatric Urology Ward of the Institute of Kidney Diseases Peshawar from August 2022 to August 2023. A total of 35 male neonates and infants with confirmed posterior urethral valves were enrolled. Antenatal bladder wall thickness measurements were retrieved from maternal ultrasound records. All patients underwent primary endoscopic valve ablation followed by urodynamic evaluation at a minimum of three months post-ablation. Detrusor underactivity was diagnosed using International Children's Continence Society criteria. Multivariate logistic regression analysis was performed to identify independent predictors of detrusor underactivity. Results: Detrusor underactivity was diagnosed in nineteen patients (54.3%). The mean antenatal bladder wall thickness was significantly greater in patients with detrusor underactivity compared to those without this condition (5.1 ± 0.8 mm versus 3.2 ± 0.7 mm; p < 0.001). A bladder wall thickness cut-off value of four millimetres demonstrated excellent predictive accuracy with an area under the receiver operating characteristic curve of 0.87. The sensitivity and specificity of this threshold were 84.2% and 75.0% respectively. On multivariate analysis antenatal bladder wall thickness emerged as the strongest independent predictor of detrusor underactivity with an adjusted odds ratio of 9.2 (95% CI: 3.1-27.5; p < 0.001). Conclusion: A significant association exists between increased antenatal bladder wall thickness and the subsequent development of post-ablation detrusor underactivity in children with posterior urethral valves. The four millimetre threshold provides a clinically useful predictor for risk stratification and early parental counselling. Keywords: Posterior urethral valves, Antenatal diagnosis, Bladder wall thickness, Detrusor underactivity, Urodynamic study, Valve ablation